Response of newly developed sunflower hybrids and varieties against downy mildew disease: Response of newly developed sunflower hybrids and varieties against downy mildew disease - D S MUTKULE; M V DHUPPE; M K GHODKHE (Journal of Oilseeds Research, 2020)
Sunflower entries under AICRP sunflower were tested in downy mildew sick plot and the data revealed that 10 entries were susceptible to the disease. Six hybrids viz., IIOSH-2, NCSH-2431, BLSFH-15005, SVSH-498, SVSH475 and LSFH-1751 were totally free from downy mildew incidence.